Modified technique of soft liner application. (4th February 2013) - Gupta, Narendra; Misra, Neeta; Kumar, Sulabh; Uppal, Saurabh
Abstract : Soft liners are materials that can be advocated successfully to manage clinical situations like atrophic edentulous ridges with flabby displaceable tissues and in cases of severely resorbed ridges which adversely affect the retention and stability of complete dentures and further enhance bone loss. Soft liner provides a cushioning effect and distributes uniform occlusal forces to compromised residual ridges. In this paper a modified technique of soft liner application in mandibular denture has been discussed.